Improved sequential Cramer-Rao type integral inequality. Issue 1 (2nd January 2018) - Rao, B. L. S. Prakasa
ABSTRACT: Cramer-Rao type integral inequalities were known for obtaining lower bounds for Bayesian risk for squared error loss functions for estimators based on fixed sample size. A sequential Cramer-Rao type integral inequality was derived by Prakasa Rao ( Proc. Andhra Pradesh Akademi of Sciences (2000) 5: 23–38). An improved version of this inequality is obtained using a recent result on improved Cauchy-Schwartz inequality due to Walker ( Statist. Probab. Lett. (2017) 122: 86–90).